Legal Information System with Housing Licensing for Administrative Efficiency Process - Krisna, Robi; Munawaroh, Faridatul; Destikarini, Fartina (Devitara Innovations, 2024)
The housing licensing administration process often faces challenges in the form of complex bureaucracy, long processing times, and lack of information integration between systems. This research aims to integrate the legal information system with the housing licensing process to improve administrative efficiency. By utilizing integrated information system technology, this research develops a platform that allows the synchronization of legal data related to housing regulations with licensing mechanisms. The methodology used includes needs analysis, system design, and efficiency evaluation through implementation case studies. The results of the study show that system integration is able to reduce processing time, improve data accuracy, and speed up decision-making. These findings are expected to make a significant contribution to optimizing the governance of housing licensing and encouraging transparency and accountability in public administration.